Defining a Standard Set of Health Outcomes for Patients With Squamous Cell Carcinoma of the Head and Neck in Spain - Arrazubi, Virginia; Cajaraville, Gerardo; Cantero, David; Giralt, Jordi; Mesia, Ricard; Monje, Florencio; Rueda, Antonio; Sistiaga, Alexander; Suarez, Jorge; Mut, Alejandro; Comellas, Marta; Lizán, Luis (Frontiers in Oncology, 2022)
Purpose A systematic, standardized collection of health outcomes during patient treatment and follow-up, relevant from the perspective of all stakeholders, is a crucial step toward effective and efficient disease management. This project aimed to define a standard set of health outcomes for patients with squamous cell carcinoma of the head and neck (SCCHN). Methods The project was led and coordinated by a scientific committee (SC). It comprised: (1) a literature review (to identify variables used during SCCHN management); (2) 1st-SC meeting (to select the variables for presentation during nominal groups-NG); (3) five NG (n=42 experts) and four interviews with patients (to reach consensus on the variables for inclusion); and (4) final-SC meeting (to review the results of NG ensuring consensus on the variables where consensus was not reached). Results Experts agreed to include the following variables in the standard set: treatment-related (treatment intent and type, response to treatment, treatment toxicity/complication, treatment completion), degree of health (performance status, patient-reported health status, pain, dysphonia, feeding and speech limitations, body image alteration, tracheotomy), survival (overall and progression-free survival, cause of death), nutritional (weight, nutritional intervention), other variables (smoking status, alcohol consumption, patient satisfaction with aftermath care, employment status), and case-mix variables (demographic, tumor-related, clinical and nutritional factors). Conclusions This project may pave the way to standardizing the collection of health outcomes in SCCHN and promote the incorporation of patients‘ perspective in its management. The information provided through the systematic compilation of this standard set may define strategies to achieve high-quality, patient-centered care.